ARSITEKTUR OMAH BUNDER - , SATRIO HASTO BROTO WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Omah bunder architecture research district is located in the village Purwodadi, Kecamatan Tepus, Kabupaten Gunungkidul, Propinsi Daerah Istimewa Yogyakarta, Indonesia. Omah bunder architecture is a type of community residential home tribal farmers in rural Java, Java island. There is a phenomenon poculiar phenomenon that has not been revealod until now, so it is still hidden architectural knowledge. Some Fenomena important is the knowledge but it does not bunder. Bunder in terms of occupancy in the form of the empirical. One other hand thore is also the trancendent values that developed in the cummunity who helped shape the architectural presence omah bunder. Through naturalistic paradigm and the phenomenological method of Yvonna S. Lincoln dan Egon G Guba (1985) dan didukung oleh Noeng Moehadjir (2000), Norman K. Denzin dan Y Yvonna S. Lincoln (2009) dan John W.Chreswell (1998)